2013
DOI: 10.1021/jp409716p
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Lipid Vesicles by a Broad-Spectrum Antiviral Peptide: Influence of Vesicle Size

Abstract: An amphipathic α-helical (AH) peptide was recently discovered that can rupture the lipid envelope of many viruses including HIV, hepatitis C, dengue, and herpes simplex. Despite its broad-spectrum activity, the AH peptide specifically targets small viruses only and does not affect large viruses. Indirect observations of virus size-specific targeting have been confirmed in a model system comprised of intact lipid vesicles on a gold substrate. Depending on vesicle size, AH peptide can promote vesicle rupture, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 57 publications
9
60
0
Order By: Relevance
“…For larger vesicles, partitioning was minimal, and indicated that the peptide most likely aggregates on the surface of large vesicles via self‐association . This finding is consistent with a previous report which indicates that AH peptide binds to, but does not rupture, large surface‐immobilized vesicles. Hence, there is a clear distinction between membrane partitioning of AH peptide in small and large vesicles.…”
Section: Methodssupporting
confidence: 93%
“…For larger vesicles, partitioning was minimal, and indicated that the peptide most likely aggregates on the surface of large vesicles via self‐association . This finding is consistent with a previous report which indicates that AH peptide binds to, but does not rupture, large surface‐immobilized vesicles. Hence, there is a clear distinction between membrane partitioning of AH peptide in small and large vesicles.…”
Section: Methodssupporting
confidence: 93%
“…Our study is inspired by the virucidal activity of an amphipathic, α‐helical (AH) peptide which is known to rupture lipid vesicles and exhibits virucidal activity against many kinds of enveloped viruses ( Scheme ). Due to the increasing resistance of many medically important viruses to conventional antiviral drugs, the AH peptide is an attractive drug candidate with a novel mechanism of action based on lipid membrane solubilization .…”
Section: Methodsmentioning
confidence: 99%
“…[60] However,t his AH peptideo nly ruptures adsorbed vesicles below ac ertain diameter,a nd QCM-Dm easurements identified that the efficiency of vesicle rupture was inversely relatedt o vesicle size. [61] Kinetic analysiso ft he QCM-D measurement data indicated that cooperative peptide binding leads to pore formation and vesicle rupture, whereas noncooperative binding does not cause vesicle rupture. Combined measurement approaches involving QCM-D and ellipsometrye xperiments have further identified that ac riticald ensity of peptide-induced pores form in al ipid vesicle before ruptureo ccurs.…”
Section: Membrane-peptide Interactionsmentioning
confidence: 99%